ANALISIS SEKTOR POTENSIAL YANG BERPENGARUH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BOVEN DIGOEL 2007-2011 - samel w ririhena (Faculty Of Economics and Business, Musamus University, 2018)
From the results of this study found that based on the Growth analysis, overall sector field effort in the Regency Boven Digoel period 2007-2011 has a positive growth except Electricity and Clean Water sector have negative growth in 2010 are registration-7,11 and on the Financial, Rent, and Business Services sektor in 2011 as much as -20,07. Sector base / superior sectors (LQ>1) based on analysis Location Quotient (LQ) namely the Agricultural sector, Industry Processing sector, and Building sector. Through analysis Shift Share classic known sector that have the skills competitive namely Mining and Quarrying sector, Electricity and Clean Water sector, Building sector, Trade, Hotels and Restaurants sector, and Financial, Rent, and Business Service sector. Keywords : Economic Growth, Growth analysis, Location Quotient (LQ), Shift Share Classic.